2006
DOI: 10.1097/01.paf.0000201108.24172.cf
|View full text |Cite
|
Sign up to set email alerts
|

Deaths From Drug Overdose and Toxicity in Turkey

Abstract: Turkey is located on the main overland connection between Asia and Europe, making the country potentially vulnerable to drug trafficking and its associated harms. The aim of the present study is to explore the frequency of all deaths from drug overdose and toxicity in Turkey and to describe some of the characteristics of these deaths. We collected data on all deaths from drugs in Turkey between 1997 and 2001 using records from the Council of Forensic Medicine. Data obtained from autopsy reports were retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…This is in line with other studies, although some studies found that most of the deaths occurred in public spaces, usually in the streets (3,5,8). …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is in line with other studies, although some studies found that most of the deaths occurred in public spaces, usually in the streets (3,5,8). …”
Section: Discussionsupporting
confidence: 92%
“…However, when the number of people who are really threatened by drug overdose is monitored, the men-women ratio is reduced to 1:5, which suggests that female drug users are exposed to a similar risk as male (29,31). Individuals who died of drug abuse were averagely older in the pre- and post-war sub-period than during the war, while in the entire period they were on average in their late twenties and early thirties, which corresponds to reports in the literature (4,5,8,29,30). This also confirms that, contrary to the popular belief, young, inexperienced drug users are not in the greatest danger of drug overdose (13,14).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…They are a valuable indicator of dimensions of the drug abuse problem in a country or a region, especially when interpreted along with other indicators (1,2). Studies have shown that, similarly to other mortality causes (3)(4)(5), certification of drug abuse deaths presents a significant problem in the world, whether they are overdose related deaths or other deaths resulting from drugs misuse (6,7).…”
Section: Introductionmentioning
confidence: 99%